The Position and Implementation of Pancasila in the Life of the Indonesian Nation and State - Sitorus, Rolib; Saragih, Joy Zaman Felix; Wilim, Anastasia; Lauvender, Felix Tommy; Fernando, Fernando; Wijaya, Gavin Timberlake; Jessen, Jessen; Vivien, Vivien (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2025)
The purpose of this research is to find out and investigate the place and application of Pancasila in the life of society and the state in Indonesia. The formation of values, conventions, and legal systems that govern the life of the nation and state is highly dependent on Pancasila as the basis of the state. The research method used in scientific articles is a normative research method that uses a conceptual approach based on actual cases as well as an approach in norms as well as various legal regulations and real practices of people's lives. The diversity of ethnicities, religions, and customs form a diverse Indonesian society, which Pancasila wants to unite. The ideals of justice and unity, which uphold the principles of a just and civilized humanity, are the embodiment of Pancasila as the foundation of the state in daily life. However, there are various obstacles in the implementation of Pancasila in various fields, such as the social, political, and economic fields. Therefore, efforts are needed to remain sustainable in maintaining the relevance and implementation of Pancasila in the dynamics of the life of the nation and state of Indonesia.